STUDENT’S PERCEPTIONS TOWARDS THE QUALITY OF LIBRARY SERVICE AT THE COLLEGE OF PHARMACY MUHAMMADIYAH TANGERANG DURING THE PANDEMIC COVID-19 - Anim PURWANTO; Uswah USWAH (Journal of Education and Leadership in Education, 2022)
The purpose of this study was to determine students' perceptions towards the quality of library service at the College of Pharmacy Muhammadiyah Tangerang during the pandemic Covid-19. The research is a descriptive study with a quantitative approach. Assessment of the LSQA scale is used in this study to assess the quality of library services which include library infrastructure, library collections, library staff and library services. The research sample was 100 students using random sampling technique. The technique of data collection used was questionnaire distribution. While the technique of data analysis used is descriptive statistics with data processing using SPSS version 25. The steps in data analysis techniques are data presentation (table), measurement of central symptoms (mean, median and mode), calculating standard deviation, discussion and drawing conclusions. The results showed that the quality of library services at the College of Pharmacy Muhammadiyah Tangerang was very good with a score of 42%. Students' perceptions of library infrastructure have a score of 53%, library collections and library employees with each score of 44% and are considered very good by students. Meanwhile, students' perceptions of library services were considered good enough by students with a value of 44%. So that library services at the College of Pharmacy Muhammadiyah Tangerang need to be improved through service accuracy, service speed, IT support in the library and students can access information in the library easily.